Railroad bridge dynamics and ratings : IDEA program final report, for the period May 2013 through November 2014 - Bollinger, Kevin (IDEA Programs, Transportation Research Board of the National Academies, 2015)
Bridge rating calculations are performed to determine the safe capacity of existing structures. The American Railway Engineering and Maintenance-of-Way Association (AREMA) Manual for Railway Engineering (MRE) is the current recommended practice used by the great majority of railroads in North America. The Foreword to MRE Chapter 15, "Steel Structures," limits the application of the chapter to freight train speeds of up to 70 mph, and passenger train speeds of up to 90 mph. Therefore, the chapter provisions do not provide a method to calculate a bridge rating for train speeds beyond 90 mph. As speeds increase, impact values either increase or decrease depending on the dynamic characteristics of the bridge structure and equipment using the track. Currently, Amtrak is operating high-speed passenger trains at speeds of up to 150 mph on the Northeast corridor. The research described in this report investigates impact factors for speeds above 90 mph to be used in capacity ratings of existing bridges. To accomplish this, basic structural dynamic methodologies and current structural engineering codes and procedures are utilized in order to propose an impact evaluation methodology consistent with current North American railroad bridge practice